Предмет: Алгебра, автор: den1217

упростить выражение: 5/12×(2 2/5x-4y)+7/15×(5x+2 1/7)​

Ответы

Автор ответа: MuhammadGulu
1

Ответ:

 \frac{5}{12}(2 \frac{2}{5}  x - 4y) +  \frac{7}{15} (5x + 2 \frac{1}{7} ) =  \frac{5}{12} ( \frac{12}{5} x - 4y) +  \frac{7}{15} (5x +  \frac{14}{7} ) = x -  \frac{5}{3} y +  \frac{7}{3} x +  \frac{14}{15}  =  - 1 \frac{2}{3} y + 3 \frac{1}{3} x +  \frac{14}{15}

Автор ответа: ludmilaksenija2005
0

Объяснение:

5/12(2 2/5х-4у)+7/15(5х+2 1/7)=

=5/12(12/5х-4у)+7/15(5х+15/7)=

=х-5/3у+7/3х+1=1 7/3х-5/3у+1=

10/3х-5/3у+3/3=(10х-5у+3)/3

Похожие вопросы
Предмет: Английский язык, автор: алёша3222227